Case Report: Mycosis fungoides as an exclusive manifestation of common variable immunodeficiency in a family with a NFKB2 gene mutation - Spangenberg, María Noel; Grille, Sofía; Simoes, Camila; Brandes, Mariana; Garcia-Luna, Joaquín; Catalán, Ana Inés; Ranero, Sabrina; Boada, Matilde; Brugnini, Andreína; Trias, Natalia; Lens, Daniela; Raggio, Víctor; et al. (Frontiers in Oncology, 2023)
Common variable immunodeficiency disorders (CVIDs), which are primary immunodeficiencies characterized by the failure of primary antibody production, typically present with recurrent bacterial infections, decreased antibody levels, autoimmune features, and rare atypical manifestations that can complicate diagnosis and management.Although most cases are sporadic, approximately 10% of the patients may have a family history of immunodeficiency. Genetic causes involving genes related to Bcell development and survival have been identified in only a small percentage of cases.Case presentation: We present the case of a family with two brothers who presented with mycosis fungoides as an exclusive symptom of a common variable immunodeficiency disorder (CVID). Whole-exome sequencing of the index patient revealed a pathogenic variant of the NFKB2 gene. Based on this diagnosis and reevaluation of other family members, the father and brother were diagnosed with this rare immune and preneoplastic syndrome. All CVID-affected family members presented with mycosis fungoides as their only symptom, which is, to the best of our knowledge, the first case to be reported.Conclusions: This case highlights the importance of high-throughput sequencing techniques for the proper diagnosis and treatment of hereditary hematological disorders.